Long-term infusion of nesfatin-1 causes a sustained regulation of whole-body energy homeostasis of male Fischer 344 rats - Mortazavi, Sima; Gonzalez, Ronald; Ceddia, Rolando; Unniappan, Suraj (Frontiers in Cell and Developmental Biology, 2015)
Nesfatin-1, the N-terminal fragment of nucleobindin 2 (NUCB2), is an 82 amino-acid peptide that inhibits food intake and exerts weight-reducing effects. Nesfatin-1 has been proposed as a potential anti-obesity peptide. However, studies to date have mainly focused solely on the acute satiety effects of centrally administered nesfatin-1. The main objective of our studies was to characterize the long-term/chronic effects of peripheral administration of nesfatin-1 on whole-body energy balance and metabolic partitioning in male Fischer 344 rats. Short-term (1 day) subcutaneous infusion of nesfatin-1 (50 µg/kg body weight/day) using osmotic mini-pumps increased spontaneous physical activity and whole-body fat oxidation during the dark phase. This was accompanied by decreased food intake and basal metabolic rate compared to saline infused controls. On the seventh day of nesfatin-1 infusion, cumulative food intake and total spontaneous physical activity during the dark phase were significantly reduced and elevated, respectively. Meanwhile, intraperitoneal injection of nesfatin-1 only caused a dark phase specific reduction in food intake and an increase in physical activity. NUCB2 mRNA expression in the brain and stomach, as well as serum NUCB2 concentrations were significantly reduced after 24 h fasting, while a post-prandial increase in serum NUCB2 was found in ad libitum fed rats. Collectively, our results indicate that chronic peripheral administration of nesfatin-1 at the dose tested, results in a sustained reduction in food intake and modulation of whole body energy homeostasis.